Ukraine science personnel potential in global trends (Economics and region, 2024)
This study focuses on the dynamics of research personnel in Ukraine and their position within global trends. In recent decades, leading countries have implemented strategies aimed at fostering innovation and strengthening their scientific and technical capacities. High-tech industries, supported by innovation, have become a crucial factor for robust economic growth and are expected to determine the competitiveness of nations in the future. The development of these industries relies heavily on a strong scientific and technical foundation, where human capital plays a key role. This paper aims to analyze the trends in the number of researchers engaged in research and development (R&D) activities globally, focusing on top 50 countries and Ukraine. The study employs a novel "speed and acceleration analysis" method developed by the authors, which allows for a nuanced understanding of changes in the number of researchers over time. The results show that, globally, there has been a significant increase in the number of researchers, particularly in high-tech industries. However, this growth remains insufficient to fully meet the global demand for technological advancement. In Ukraine, the number of researchers has been steadily decreasing, placing it behind even some African countries such as Egypt and Tunisia. The study also presents a detailed grouping of countries based on the dynamics of researcher numbers, revealing that many nations experience fluctuations in the short term, with both acceleration and deceleration phases observed. In the long term, the situation in Ukraine has reached critical levels, with over a decade of accelerated decline in the number of researchers. The findings highlight the urgent need for policy interventions to reverse the negative trend in Ukraine’s scientific and technical workforce and underscore the importance of developing human capital as a central component of national scientific and technological potential.
Keywords: high-tech industries; scientific and technical capacity; economic growth; researchers; global trends; Ukraine